Phương pháp ước lượng LASSO: Cơ sở toán học và ứng dụng - Bùi Thị Thiện, Mỹ (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This paper introduces the LASSO estimation method for regression analysis. Similarly OLS estimation method, LASSO finds estimates of the parameters of a regression model by minimizing the objective function as the sum of squared-residuals. However, LASSO imposes a constraint on the sum of absolute values of parameters in the model by a tuning parameter. The paper presents an overview of the meaning and the mathematical background of LASSO. Besides, the paper introduces an empirical case applying LASSO estimation method to identify intrinsic factors affecting the ROA and ROE of Vietnamese joint stock commercial banks. The results show that LASSO has eliminated factors that do not affect ROA and ROE, providing a simpler regression model with a smaller MSE than OLS method does, although this improvement is not significant
Keywords: Regression; LASSO; Shrinkage model